El problema del multicubrimiento: una aplicación para la selección de paradas en la red de transporte de la Ciudad de México - Gutiérrez Andrade, Miguel Angel (2003)
In this paper an heuristic algorithm is developed. Its implementation is developed as well, in order to solve a sampling problem in the urban transportation network in Mexico City. The problem consist of the selection of at least 2 points (stops) on each of the 236 routes in the study comprising a total of 8390 stops. This problem is presented as a multicover problem subject to 236 restrictions and 8390 binary variables. Given that this an NP-hard problem, it was implemented an heuristic algorithm to determine the sampling points.